Fulfill the Responsibility to Ensure the Civil Rights - The Policy Implications for Tectonic Government in Vietnam Today - Viet, Tran Quoc (VNU Journal of Science: Policy and Management Studies, 2020)
Ensuring civil rights is the responsibility of the State. This research aims to define the policy implications for tectonic Government to fulfill the responsibility to ensure the civil rights in Vietnam today. By summarizing some of the recent prominent results of the Vietnamese Government, the article provides the policy implications in the fields of politics, economy, culture-society, legal, international cooperation. The final goal of these policies is bring the satisfaction and happiness to people.